An international feminist challenge to theory - Demos, Vasilikie P.; Segal, Marcia Texler, 1940- (JAI, 2001)
In this volume, 15 feminist scholars from five continents, who participated in the 1998 conference co-sponsored by Research Committee 32, Women in Society, of the International Sociological Association (WISISA) and the Centre for Research and Teaching on Women at McGill University, consider, critique and construct theories of society. Their papers examine four inter-related themes: an explicit or implicit acknowledgment and critique of the European Enlightenment as a basis for the modern production of knowledge; the use and utility of "gender" as a concept; problems and solutions in feminist theories of development; and the place of feminism in the production of knowledge and on-the-ground change. Each paper reflects the author's experience as a researcher, theorist or change agent, as well as the discussion and dialogue of the five-day conference.
Keywords: Feminism.; Gender identity.; Feminism & feminist theory.; Social Science -- Feminism & Feminist Theory.; elektronické knihy; electronic books